Pengembangan Asesmen Kinerja untuk Menilai Keterampilan Proses Sains Terintegrasi Siswa pada Konsep Ekosistem - Nurfitriani, Nurfitriani; Wulan, Ana Ratna; Anggraeni, Sri (Assimilation: Indonesian Journal of Biology Education, 2018)
This study was conducted to analyze about the development of the performance assessment in assessing the integrated science process skills on the concept of habitat in the ecosystem. The integrated science process skills require a higher knowledge based to be able to carry out a variety of science process skills in an integrated learning. Performance assessment development process starting from the preparation of the performance assessment, the assessment test in order to obtain the parts repaired and the device obtained a more complete assessment of performance. Descriptive method is used in this research. The study provides information that the instruments developed already proper for use to assess the integrated science process skills on the concept of habitat in the ecosystem. Judging from the achievement test scores on the implementation class development fromÂ  the previous trials with an average score of integrated KPS by (70.00) and increased at the stage of implementation of (73.11) with good category. It also developed an effective performance assessment to assess the the integrated science process skills with validity of the assessment of performance has increased in every test try. The first trial has the validity number (0,56), the second trials has validity number (0.81) and the last trials has the validity number (0.86). It can be concluded the assessment was developed capable to assessing the integrated science process skills of students with very high the last valdity value.